Conventional and Alternative Strategies to Cope With the Subtropical Climate of Tokyo 2020: Impacts on Psychological Factors of Performance - Coudevylle, Guillaume R.; Sinnapah, Stéphane; Robin, Nicolas; Collado, Aurélie; Hue, Olivier (Frontiers in Psychology, 2019)
The thermal discomfort caused by a hot or tropical (i.e., hot and humid) climate can have negative effects on human performance. The 2020 Summer Olympic and Paralympic Games will take place in Tokyo’s hot and humid summer period, possibly exposing athletes to very high environmental stressors. In addition to technical, tactical, physical and nutritional preparation, very high-level athletes need an optimal psychological state to turn in their best performances, especially in terms of emotional control, concentration and motivation. Yet, the tropical climate (i.e., TC) can have many negative effects on these factors. Better understanding of the negative effects of TC and the strategies to manage them might be crucial for competitors, coaches and their teams in Japan. For example, cooling interventions before, during and/or immediately after exercise have been extensively presented in the physiological literature. However, the effects of these interventions on psychological states and the use of psychological techniques like cooling intervention strategies have rarely been explored. This article proposes to take stock of the knowledge on the strategies that help athletes to psychologically cope with TC during competition.